2012
DOI: 10.1007/s00330-012-2421-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the histopathological grade of hepatocellular carcinoma using qualitative diffusion-weighted, dynamic, and hepatobiliary phase MRI

Abstract: • Predicting the histopathological grade of hepatocellular carcinoma (HCC) preoperatively is important. • Diffusion-weighted imaging (DWI) and subtraction imaging are recently developed MR techniques. • Retrospective study showed DWI and subtraction imaging helps predict HCC grades. • Management of patients with HCC becomes more appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 15 publications
1
33
1
Order By: Relevance
“…Previous studies that investigated these imaging features tended to have a higher proportion of tumors with intratumoral fat and encapsulation than in our study (36)(37)(38). A few previous studies consistently found that higher signal intensity on diffusion-weighted images was associated with less histologic differentiation, and a possible relationship between ADCs and histologic differentiation and microvascular invasion has been suggested (39)(40)(41)(42). However, in our study, neither histologic differentiation nor signal intensity or ADC on diffusion-weighted images was a significant predictor of early HCC recurrence.…”
Section: Gastrointestinal Imaging: Prediction Of Early Recurrence Of supporting
confidence: 60%
“…Previous studies that investigated these imaging features tended to have a higher proportion of tumors with intratumoral fat and encapsulation than in our study (36)(37)(38). A few previous studies consistently found that higher signal intensity on diffusion-weighted images was associated with less histologic differentiation, and a possible relationship between ADCs and histologic differentiation and microvascular invasion has been suggested (39)(40)(41)(42). However, in our study, neither histologic differentiation nor signal intensity or ADC on diffusion-weighted images was a significant predictor of early HCC recurrence.…”
Section: Gastrointestinal Imaging: Prediction Of Early Recurrence Of supporting
confidence: 60%
“…A correlation between heterogeneous arterial enhancement and worrisome biologic features has not been consistently observed, however (68). Whether the intensity, as opposed to the heterogeneity, of arterial phase enhancement predicts tumor grade, microvascular invasion, or other prognostic features is controversial (69,70). Additionally, the rate at which tumors appear to "wash out" may be important.…”
Section: Feature Commentsmentioning
confidence: 99%
“…Retrospective studies have suggested that restricted diffusion, as assessed by signal intensity ratio or ADC measurement, can be used to predict higher tumor grade (69,147,148), presence of progenitor cell markers (107), microvascular invasion (149), and early recurrence after resection (150). Results have been inconsistent, however, and some investigators have found no correlation between ADC and HCC tumor grade (151).…”
Section: Ancillary Features That Favor the Diagnosis Of Malignancy Bumentioning
confidence: 99%
“…It has actually become common to encounter cases where hypervascular HCC or nodule-in-nodule HCC that is undetectable by MDCT is detected in a routine screening by EOB-MRI because of early enhancement in the arterial phase or clear hypointensity in the hepatobiliary phase [11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103]. Furthermore, studies comparing the diagnostic performance of EOB-MRI and MDCT for hypervascular HCC have shown that EOB-MRI is superior or, at the very l...…”
Section: Diagnostic Algorithmmentioning
confidence: 99%